2018
DOI: 10.1021/acsnano.8b00417
|View full text |Cite
|
Sign up to set email alerts
|

Minimalist Prion-Inspired Polar Self-Assembling Peptides

Abstract: Nature provides copious examples of self-assembling supramolecular nanofibers. Among them, amyloid structures have found amazing applications as advanced materials in fields such as biomedicine and nanotechnology. Prions are a singular subset of proteins able to switch between a soluble conformation and an amyloid state. The ability to transit between these two conformations is encoded in the so-called prion domains (PrDs), which are long and disordered regions of low complexity, enriched in polar and uncharge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(94 citation statements)
references
References 65 publications
4
90
0
Order By: Relevance
“…In this subclass of amyloids, which are self-perpetuating and infectious, sequence determinants have been elusive for years, since cryptically encoded by rather long (at least 60 residues) and disordered sequences, containing a few amino acid types (i.e., low-complexity regions) rich of Tyr, Gly, and polar residues (mostly Gln and Asn) [90,[93][94][95], which argue for the involvement of hydrogen bonds, van der Waals, and π-π stacking interactions [96][97][98]. Short linear sequence motifs rich in polar residues (e.g., SYSGYS from human FUS protein, or GNNQQNY from yeast Sup35) have also been recognized as "nucleation centers" or "soft-amyloid cores", effectively promoting both spontaneous and seeded aggregation in proteins [99,100], and natural and synthetic peptides [101][102][103].…”
Section: Relevance Of Electrostatic Charges On Fibrillationmentioning
confidence: 99%
“…In this subclass of amyloids, which are self-perpetuating and infectious, sequence determinants have been elusive for years, since cryptically encoded by rather long (at least 60 residues) and disordered sequences, containing a few amino acid types (i.e., low-complexity regions) rich of Tyr, Gly, and polar residues (mostly Gln and Asn) [90,[93][94][95], which argue for the involvement of hydrogen bonds, van der Waals, and π-π stacking interactions [96][97][98]. Short linear sequence motifs rich in polar residues (e.g., SYSGYS from human FUS protein, or GNNQQNY from yeast Sup35) have also been recognized as "nucleation centers" or "soft-amyloid cores", effectively promoting both spontaneous and seeded aggregation in proteins [99,100], and natural and synthetic peptides [101][102][103].…”
Section: Relevance Of Electrostatic Charges On Fibrillationmentioning
confidence: 99%
“…The rational design and usage of defined amyloid‐based nanostructures are still being hindered by several issues, which include the high aggregation propensity of amyloidogenic β‐sheet‐forming sequences, the lack of control over the self‐assembly process and the difficulty of predicting the final supramolecular architecture from the primary sequence . In contrast to polymers built on covalent bonds, bottom‐up polypeptide amyloid self‐assembly relies on the formation of a complex and organized network of intermolecular noncovalent interactions . The difficulty of controlling amyloid formation arises from this delicate interplay between several factors triggering nucleation and elongation,7,13a including hydrophobic interactions, hydrogen bonding, electrostatic interactions, and environmental conditions .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the de novo design of prion-inspired self-assembling peptides for nanotechnology applications remained essentially unexplored. To fill this gap we rationally designed four minimalist polar binary patterned peptides bioinspired on prion sequences and exploited them for the obtention of biomaterials with unique properties [66]. The design combined the five most enriched residues in PrDs, Asn, Gln, Ser, Gly and Tyr in a binary pattern, with only seven residues in length, resulting in four heptapeptides: NYNYNYN, QYQYQYQ, SYSYSYS and GYGYGYG.…”
Section: Nanomaterials Based On Prionsmentioning
confidence: 99%
“…We assessed the electrocatalytic ability of our four self-assembled nanostructures by exposing them to copper (II) as an oxidizing agent, in the presence of distilled pyrrole vapor. The fibrils catalyzed efficiently the polymerization of individual pyrrol moieties into a macromolecular polypyrrole (PPy) material ( Figure 2) [66]. Importantly, not all the peptides exhibited the same electrocatalytic activity, which indicated that this property was sequence dependent and, accordingly, that it can be potentially tuned to develop synthetic prion-inspired nanodevices with different catalytic properties.…”
Section: Nanomaterials Based On Prionsmentioning
confidence: 99%
See 1 more Smart Citation